Are cataract surgery referrals to public hospitals in Australia poorly targeted?. (10th October 2017) - Do, Vu Quang; McCluskey, Peter; Palagyi, Anna; Stapleton, Fiona J; White, Andrew; Carnt, Nicole; Keay, Lisa
Abstract: Importance: Referral letters constitute the first step on the pathway to cataract surgery; however, little is known on how effective referral letters are in providing adequate information to triage patients and inform surgical prioritization. Background: Benchmarking exercises are important to document referral processes and to identify areas where improvements can be made. Design: Cross‐sectional study with longitudinal follow‐up conducted at two metropolitan public hospitals in New South Wales, Australia. Participants: A total of 400 sequential cataract referral letters. Methods: An audit of cataract referral letters was performed and content benchmarked against international prioritization tools. Medical records were reviewed 1 year following referral. Main Outcome Measures: Referral quality and waiting times. Results: Two‐thirds of patients referred for cataract surgery were yet to have their initial hospital appointment in the year following referral (65%, 245/376). One half of referrals seen in clinic (49%, 64/113) were not listed for cataract surgery. Multivariate analysis revealed referral letter content was not indicative of surgical booking, with the major predictors being hospital‐recorded visual acuity and grading of cataract ( P  < 0.0001). Referral content lacked sufficient detail to apply prioritization tools developed in other settings. Conclusion and Relevance: This audit highlights a disconnect between referral letter content and hospital assessment of patients. Current referrals to public hospitals are poorly targeted, with high numbers of referred patients not proceeding to surgery. Patients commonly waited over 1 year to have their ophthalmic assessment at these public hospital eye clinics, revealing lengthy 'wait‐for‐waits' as a barrier to care. Standardized referral templates may facilitate improvement of referral pathways and shorten waiting times.